Influence of precursor concentration and temperature on the formation of nanosilver in chemical reduction method - N. Ahmad; Ang, B.C.; M.A. Amalina; Bong, C.W. (Penerbit Universiti Kebangsaan Malaysia, 2018)
Nanosilver particles (NSPs) were produced by the reduction of silver nitrate using glucose as reducer, poly (vinyl pyrrolidone) as stabilizer and sodium hydroxide as reaction enhancer. Two parameters were investigated which are silver nitrate concentration (0.1 M, 0.5 M and 1.0 M) and reaction temperature (60°C and 80°C). Through spectral analysis using ultraviolet-visible spectrophotometer (UV-vis), all the samples recorded the maximum peak in the range of 384-411 nm which verified the formation of NSPs. TEM images showed the nanoparticles have spherical shape with the size range of 25-39 nm. Particle size and zeta potential analysis recorded the hydrodynamic size of nanoparticles in the range of 85-105 nm and the zeta potential ranging from -25 to -30 mV, under the pH value of 8. X-ray diffraction analysis showed that the NSPs have face center cubic (FCC) structure. All the produced NSPs surprisingly showed ferromagnetic-like behaviour based on the magnetization curves. FTIR result confirmed the presence of poly (vinyl pyrrolidone) on the NSPs surface. Furthermore, at the reaction temperature 60°C, the crystallite size, physical size as well as hydrodynamic size increased as the precursor concentration increased from 0.1 M to 0.5 M. However, as the precursor concentration further increases to 1.0 M, the size become smaller due to incomplete reduction process. In contrast, at 80°C, the sizes was gradually increased as the precursor concentration increases up to 1.0 M. In terms of controlled precursor concentration, the crystallite size and physical size become smaller as the temperature increases.